E0563 Implantation of left ventricular epicardial lead guided by overlay ref for cardiac resynchronisation therapy. (17th November 2010) - Kai, Tang; Dongdong, Zhao; Yawei, Xu
Abstract : Objective: This study was to report our initial experiences with cardiac resynchronisation therapy (CRT) guided by Overlay Ref for the treatment of heart failure. Methods: Eleven patients with heart failure were enrolled in this study, with (24%±11%) of mean left ventricular ejection fraction (LVEF) and (78 mm±13 mm) of left ventricular end-diastolic dimension (LVEDD). Using Overlay Ref technique, a reference image (inverted) of coronary sinus (CS) and its branches was faded into the live fluoroscopic image. The guidewire (originally designed for percutaneous transluminal coronary angioplasty) could be placed to the target branch of CS guided by Overlay Ref image. Then the left ventricular epicardial lead was positioned to the desired spot through the guidewire. Results: All patients were successfully implanted with LV leads guided by Overlay Ref. Exposure time to X-ray was (19.7 min±14.2 min). And the total duration of procedure was 99 min±42 min). 2 weeks after the implantation procedure, ultracardiography (UCG) test showed that LVEF of this patient was raised to (28%±9%). Conclusion: Overlay Ref technique could facilitate the procedure of LV lead implantation for CRT.